FEV1 and total cardiovascular mortality and morbidity over an 18 years follow-up population-based prospective EPIC-NORFOLK study - Ching, Siew Mooi; Chia, Yook Chin; Lentjes, Marleen A. H.; Luben, Robert; Wareham, Nicholas; Khaw, Kay Tee (BioMed Central, 2019)
Background Our study aimed to determine the association between forced expiratory volume in one second (FEV1) and subsequent fatal and non-fatal events in a general population.